Community Empowerment Multiculturalism Through the Digitalization of Village Websites as a Medium For Religious Moderation and MSMEs Promotion - Dewi Iriani; Hariyadi Fajar Nugroho; Ahmad Muhammad; Elyza Devi Pramest; Salsa Alvalinnas Alitsa Minha; Shelly Choirunisa; Syafira Khoirunnisa (CogniSpectra Publishing, 2026)
ABSTRACT Background: Digital-based community service is a strategic approach to addressing the social and economic challenges facing villages in the era of digital transformation. This program aims to empower the multicultural community of Gedongrejo Village by utilizing the village website as a public information medium, strengthening religious moderation, and promoting information technology-based MSMEs. Contribution: This community service activity contributes to improving digital literacy among village officials and the community, strengthening social cohesion through religious moderation content in digital spaces, and opening up access to digital promotion for local MSMEs. Method: The community service method is carried out in a participatory manner with stages of needs analysis, design and development of village websites based on informatics engineering, training in system management and digital literacy, assistance in content production, and monitoring and evaluation of website utilization. Results: The community service results indicate that the village website was successfully implemented as a public information system and community empowerment tool. The website was used to disseminate village information, publish content on religious moderation, and serve as a digital showcase for MSMEs, resulting in increased access to information and community utilization of digital technology. Conclusion: This community service program proves that digitalization of village websites based on information technology engineering can be an effective instrument in empowering multicultural communities, strengthening religious moderation, and providing initial support for the sustainable development of local MSMEs.